The relationship between firm size and exports in the context of merger review in South Africa : is the international competitiveness public interest clause of the Competition Act valid - Aproskie, Jason (University of Cape Town, 2014)
Includes bibliographical references (leaves 32-34). === According to the Competition Act of South Africa, proposed mergers, if rejected on the grounds of anti-competitive effects as well as the efficiency considerations, may be passed on certain public interest grounds. The fourth public interest clause potentially allows mergers to be passed should the merged firm become more able to compete in international markets. This paper interprets the clause to refer to a relationship between firm size and exports, and investigates this supposed relationship and, in so doing, the validity of the clause. It is found that firm size is positively related to export propensity, the likelihood of exporting any output. However, firm size is found to be unrelated to the intensity of exporting, the proportion of output that is exported by the firm. This paper covers new areas of research, and its conclusions call into question the inclusion of the relevant public interest clause in the Competition Act.